Resurgence of Diphtheria – A case report - Dr. Mita D. Wadekar; Dr. Sathish J.V (Tropical Journal of Pathology and Microbiology, 2018)
Diphtheria is a highly infectious and one of the most common causes for childhood mortality. In developed countries, diphtheria has been completely eradicated with the introduction of effective immunization program. In developing countries like India, the incidence of this disease has declined with immunization. But resurgence has been reported from many parts of India. Poor immunization coverage and failure to take booster doses is responsible for persistence of diphtheria. Here we report a case of diphtheria in a 6 year old boy from Chamarajanagar district.